Transdisciplinarity in the university: discourse and practice - DOI: 10.3395/reciis.v3i3.270en - Aleixina Maria Lopes Andalécio (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This article presents discussions and partial results of a piece of doctoral research centered on the questions raised by the new forms of production and organization of knowledge, guided by the discourse and practice of transdisciplinarity. The latter is understood in the context of the university, as an effort to overcome the fragmentation of knowledge into disciplines and excessive specialization, in face of the complex reality of the modern world, with its relational and interconnected character. To guide the questions, the research is based on the presuppositions that there is an epistemological, practical, social, and political distance between the discourse and the practice of transdisciplinarity. The empirical terrain is represented by the analysis of two large institutional transdisciplinary projects implemented at the Federal University of Minas Gerais in the late 1990s. In the methodology, thematic document analysis techniques, in-depth interviews, and direct observation are used. The results reached so far indicate that even researchers who have a strong discourse in favor of transdisciplinarity still work in a disciplinary manner in practice. However, even among researchers who are called "disciplinary", there seems to be a consensus that current problems demand a different approach and transdisciplinarity presents itself as an appropriate alternative to deal with them.